Characteristics of patients treated by the Danish Helicopter Emergency Medical Service from 2014-2018: a nationwide population-based study - Alstrup, Karen (Scand J Trauma Resusc Emerg Med, 2019)
BACKGROUND: A national Helicopter Emergency Medical Service (HEMS) was introduced in Denmark in 2014 to ensure the availability of physician-led critical care for all patients regardless of location. Appropriate dispatch of HEMS is known to be complex, and resource utilisation is a highly relevant topic. Population-based studies on patient characteristics are fundamental when evaluating and optimising a system. The aim of this study was to describe the patient population treated by the Danish HEMS in terms of demographics, pre-hospital diagnostics, severity of illness or injury, and the critical care interventions performed. METHOD: The study is a retrospective nationwide population-based study based on data gathered from the Danish HEMS database. We included primary missions resulting in a patient encounter registered between October 1(st) 2014 and April 30(th) 2018. RESULTS: Of 13.391 dispatches registered in the study period we included 7133 (53%) primary missions with patient encounter: 4639 patients were air lifted to hospital, 174 patients were escorted to hospital by the HEMS physician in an ambulance, and in 2320 cases HEMS assisted the ground crew on scene but did not escort the patient to hospital. Patient age ranged from 0-99 years and 64% of the population were men. The median age was 60 years. The main diagnostic groups were cardio-vascular emergencies (41%), trauma (23%) and neurological emergencies (16%). In 61% of the cases, the patient was critically ill/injured corresponding to a NACA (National Advisory Committee for Aeronautics) score between 4 and 7 (both included). In more than one third of the missions a critical care intervention was performed. Ultrasound examination and endo-tracheal intubation were the critical care interventions most frequently performed (21% and 20%, respectively). CONCLUSION: The national Danish HEMS primarily attends severely ill or injured patients and often perform critical care interventions. In addition, the Danish HEMS provides rapid transport to highly specialised treatment for patients in the more rural parts of the country. Patients with cardio-vascular emergencies, trauma and neurological emergencies are among those patient groups most commonly seen. We conclude that the overall dispatch profile appears appropriate but emphasise that continuous development and refinement is essential.